Coadministration of Cariprazine with a Moderate CYP3A4 Inhibitor in Patients with Schizophrenia: Implications for Dose Adjustment and Safety Monitoring - Szabó, Máté; Hujber, Zoltán; Harsányi, Judit; Szatmári, Balázs; Dombi, Zsófia B.; Magyar, Gabriella; Hegedűs, Zsuzsanna; Ratskó, Piroska; Pásztor Mészáros, Gabriella; Barabássy, Ágota (Clinical pharmacokinetics, 2024)
Background Cariprazine is metabolised mainly by CYP3A4 and to a lesser extent by CYP2D6. Aim This study aimed to evaluate the effects of erythromycin, a moderate cytochrome P450 (CYP)3A4 inhibitor, on the pharmacokinetics of cariprazine in male patients with schizophrenia, and to assess the influence of CYP2D6 phenotypes on cariprazine metabolism. Methods Forty-two patients received oral doses of 1.5 mg cariprazine alone for 28 days (to reach steady state), followed by a co-administration of cariprazine 1.5 mg daily with erythromycin 500 mg twice daily (BID) and Enterol 250 mg BID for 21 days, followed by a 14-day post-treatment period. Blood samples were collected at predefined time points and analysed for cariprazine, its two active metabolites: desmethyl cariprazine (DCAR) and didesmethyl cariprazine (DDCAR), and erythromycin using validated high performance liquid chromatography-tandem mass spectrometry methods. CYP2D6 phenotypes were determined by genotyping. The pharmacokinetic parameters were calculated using non-compartmental analysis. Results Erythromycin increased the area under the curve (AUC τ ) and peak concentration ( C max ) of Total cariprazine (cariprazine + DCAR + DDCAR) by about 40–50% but did not affect the time to peak concentration ( T max ). The CYP2D6 phenotypes had no substantial effect on the pharmacokinetics of cariprazine and its metabolites, either alone or in combination with erythromycin. Cariprazine was well tolerated and safe. Conclusion The findings suggest that co-administration of cariprazine with moderate CYP3A4 inhibitors may require dose adjustment or monitoring; however, pharmacogenetic testing for CYP2D6 is not necessary for optimising cariprazine therapy. Trial Registration Trial registration number (EudraCT Number): 2018-003721-28. Date of registration: 21-SEP-2018.